Determinasi Pelatihan Kerja dan Penilaian Kerja Terhadap Kinerja Karyawan PT. Schlemmer Automotive Indonesia - Maha Putra (Universitas Pendidikan Nasional, 2021)
A company that can be said to have succeeded in developing human resources by having various kinds of skills and good knowledge is one of the efforts that a company can make to improve employee performance with Employee Training and Appraisal. This study aims to find out anything that has a major effect on performance and assessment of performance. This type of research is quantitative. The sampling method in this study is nonprobability sampling or saturated samples. The sample taken in this study may be 60 respondents. Based on the results of research and discussion, it can be denied that: 1.) Training has a positive and significant effect on Employee Performance 2) Job Appraisal has a positive and significant effect on performance. 3) By using the F test simultaneously, training and work results have an effect on employee performance.